Neuroticism and anxious attachment as potential vulnerability factors of repeat suicide attempts. (June 2018) - Pennel, Lucie; Quesada, Jean-Louis; Dematteis, Maurice
Highlights: Clinical tools to easily and efficiently screen repeat suicide attempters are lacking. Repeaters have higher neuroticism and anxious attachment than first-time attempters. These two parameters may predict a 4 times higher risk of repeat suicide-attempt. Combined with 2 other predictors, they may constitute an efficient 13-item tool. This tool may help screening suicide repeaters and referring them to more adapted care. Abstract: The recurrence risk of suicide attempts can reach 50% in the first year, each attempt increasing suicide-risk by 32%. No screening tool efficiently identifies potential repeat suicide attempters who are too often regarded as borderline personality. Our aim was to identify individual and interpersonal psychopathological dimensions that could represent a vulnerability to repeat suicide attempts. Sixty first-time and repeat suicide attempters consecutively admitted in emergency rooms were compared for fundamental dimensions of personality, patterns of attachment, personality and mental disorders using standardized questionnaires. Confounding and significantly different factors were evaluated using univariate and multivariate logistic regressions. Repeat suicide attempters differed from first-attempters by higher neuroticism and anxious attachment. Combined in an 11-item measure, these two parameters identified a 3.99 times higher risk of repeat suicide attempt. These traits associated with the other two best predictors (non-suicidal self-injury history, current psychotropic drugs) provide a vulnerability model with better screening performance compared to each factor individually. Repeat suicide attempters have more psychological features impairing emotional stability and social interactions than first attempters. Cross-sectional study design, sample size, lack of independent sample and of fearful-avoidant attachment evaluation are the main limitations. The model needs to be validated in a prospective and controlled study.